Experiences From a Combined Dermatology and Rheumatology Clinic: A Retrospective Review. Issue 5 (September 2016) - Samycia, Michael; McCourt, Collette; Shojania, Kam; Au, Sheila
Background: The Dermatology and Rheumatology Treatment Clinic is a novel multidisciplinary clinic where patients are concomitantly assessed by a rheumatologist and dermatologist. Objectives: To determine the number of patients seen in clinic, patient demographics, and most common diagnoses. Method: A retrospective review was performed over a 2-year period. Data collected included patient age, sex, dermatologic diagnosis, rheumatologic diagnosis, biopsies performed, and number of follow-up visits. Results: A total of 320 patients were seen (78% female, 22% male). The most common rheumatologic diagnoses were systemic lupus erythematosus (18%), rheumatoid arthritis (15%), psoriatic arthritis (13%), and undifferentiated connective tissue disease (8%). The most common dermatologic diagnoses were dermatitis (17%), psoriasis (11%), cutaneous lupus (7%), various types of alopecia (6%), and infections (5%). Conclusions: Skin diagnoses were often unrelated to the underlying rheumatologic diagnosis. Rheumatologists and dermatologists can both benefit from being aware of the dermatologic conditions that rheumatologic patients are experiencing.